Fabrication of multilayered Au/silica/gadolinium compound core–shell particles and their imaging properties. Issue 8 (24th May 2017) - Kobayashi, Y.; Shindo, Y.; Oikawa, T.; Tokunaga, M.; Kubota, Y.; Gonda, K.
Abstract : The present work proposes a preparation method for multilayered Au nanoparticle/silica/gadolinium compound core–shell (Au/SiO2 /GdC) particles. Silica-coated Au core–shell (Au/SiO2 ) particles with a size of 38.0 nm were prepared by a sol-gel reaction in the presence of the Au nanoparticles with a size of 15.5 nm. Multilayered Au/SiO2 /GdC particles with sizes of ca. 35–52 nm were prepared by a homogeneous precipitation reaction in the presence of Au/SiO2 particles. The computed tomography (CT) value of the Au/SiO2 /GdC colloid solution containing 4.3 × 10 −2  M Au was 344.1 HU: Its converted CT value (CT divided by Au concentration) was as large as 8.0 × 10 3  HU/M. The r 1 value of the Au/SiO2 /GdC colloid solution was as large as 3.5 mM −1  s −1 .